Degenerate matrix method for solving nonlinear systems of differential equations - Cîrulis, T.; Lietuvietis, O. (Mathematical Modelling and Analysis, 1998)
Degenerate matrix method for numerical solving nonlinear systems of ordinary differential equations is considered. The method is based on an application of special degenerate matrix and usual iteration procedure. The method, which is connected with an implicit Runge‐Kutta method, can be simply realized on computers. An estimation for the error of the method is given.First Published Online: 14 Oct 2010